Conflict of jurisdiction and freedom of religion in Malaysia: A irreconcilable right? - Abdullah, N. (2007)
Although the Federal Constitution is the supreme law of the land, the dual legal system in Malaysia basically means Muslims in the country are governed under the Islamic or Syariah law. The scope of applicable Islamic law can be discerned from the State List in the Ninth Schedule of the Federal Constitution. It includes the 'creation and punishment of offences by persons professing the religion of Islam against the precepts of that religion'. The matter relating to conversion to and renouncement of Islam is not specifically stated in the List although it is acknowledged that it is not an exhaustive list. The freedom of religion is declared in Article 11 of the Federal Constitution. With the exception of restriction on propagation of any religious doctrine or belief among Muslims, every person has the right to profess and practice.his religion. The caveat on this freedom is any act contrary to any general law relating to public order, public health or morality. Over the years a number of cases have been presented to the civil courts on matters of faith or the lack of it, with differing results . Challenges and difficulties faced by individuals in the predicament of conversion and! or renouncement seemed insurmountable with the civil courts refusing to hear the matter on the ground that they lack jurisdiction to hear the matter. The difficulty is compounded by the perception that the Syariah courts and the relevant religious authorities are biased. The fact that there has been no Syariah court order sanctioning or confirming renouncement of Islam does little to assuage the fear and concern of the affected individuals and society at large. It must be acknowledged that renouncement of Islam is a grave sin in the eyes of Muslims and has been made an offence in certain states in Malaysia. Unfortunately this unhappy state of affairs is made worse by the lack of provisions and uniformity in state legislation governing the administration of Islamic law. The current mindset of religious authorities concerning such cases is to assist in every way, to the extent of detaining the person for the purpose of 'education', to ensure that the person does not stray from the true religion. There is also the fear that if such cases are allowed, the ummah or the Muslim community will be under the threat of its followers abandoning their faith. The current political climate and reality exacerbate the need to champion the cause of Islam. An analysis of relevant cases reveals an increasing trend of reluctance on the part of civil court judges to 'interfere' on 'matters of Islamic law'. The question remains - is the pronouncement or renouncement of faith a constitutional right of the individual or is it a matter of Islamic law and therefore is within the exclusive jurisdiction of the Syariah courts? Are the various provisions in the state legislation governing matters of faith in conflict with freedom of religion? In the final analysis, an attempt is made to assess the Viability and feasibility of legislating on faith in a multi-racial and multi-religious country like Malaysia.